Estetika Komoditas pada Opera Batak Si Mardan - Ilham Rifandi; Susandro Susandro; Ikhsan Satria Irianto (SENDRATASIK UNP, 2023)
Globalization affects every line of human cultural life, including theatre arts. As an important subsystem in culture, art is a manifestation of the complexity of human culture which is embedded coherently in its cultural identity. The city of Medan is a city with relatively dynamic theater development which has various groups with various theater genres. This tendency also gives rise to a tendency to use traditional culture as the basic material for creating theatrical works, for example, the Bandar Peran group. This group staged the work "Opera Batak Si Mardan" which involved the charm of Batak Toba and Malay culture simultaneously. In this research, it was found that the Bandar Peran group used a dual orientation imagination in its creation process and the traditional idiom used led to postmodern aesthetic tendencies. This research uses qualitative research methods to understand in depth the conditions and phenomena in the field. Apart from that, this article is also intended as a form of inventive criticism so that the content of the article uses the critical framework explained by Benny Yohanes.Globalisasi mempengaruhi setiap lini kehidupan kebudayaan manusia, termasuk seni teater. Sebagai subsistem penting dalam kebudayaan, seni merupakan wujud kompleksitas kebudayaan manusia yang tertanam secara koheren dalam identitas budayanya. Kota Medan merupakan kota dengan perkembangan teater yang relatif dinamis yang mempunyai berbagai kelompok dengan genre teater yang beragam. Kecenderungan tersebut juga memunculkan kecenderungan untuk menggunakan budaya tradisional sebagai bahan dasar penciptaan karya teater, misalnya kelompok Bandar Peran. Kelompok ini mementaskan karya “Opera Batak Si Mardan” yang melibatkan budaya Batak Toba dan Melayu secara bersamaan. Maka dalam artikel ini ditemukan hasil bahwa kelompok yang menggunakan imajinasi orientasi ganda dalam proses penciptaannya dan idiom tradisional yang digunakan mengarah pada kecenderungan estetika postmodern. Penelitian ini menggunakan metode penelitian kualitatif untuk memahami secara mendalam kondisi dan fenomena di lapangan. Selain itu, artikel ini juga ditujukan sebagai bentuk kritik inventif agar isi artikel menggunakan kerangka kritis yang dijelaskan oleh Benny Yohanes.